ANALISIS SPASIAL KEPADATAN LARVA PADA WILAYAH KASUS DEMAM BERDARAH DENGUE DI KELURAHAN SENDANGMULYO KOTA SEMARANG - Wahyu Supriyanto; Praba Ginandjar; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Sendangmulyo Village is one of the dengue endemic areas with the 4th highest incident rate (IR) in Tembalang District. One of the factors that influence the incidence of dengue is the high density of Aedes spp. larvae. Be required control strategies affectively and efficiently. To support the success of efforts to eradicate the vector, dengue entomology surveys is a must by using House Index (HI), Container Index (CI), and Breteau Index (BI). Spatial analysis in GIS can be used determine the pattern of distribution and areas of dengue potential transmission. The purpose of this study was to spatially analyze the presence and density of Aedes spp. larvae in the area of dengue cases in Sendangmulyo Village, Semarang City. This research is an observational descriptive study with a spatial approach. The number of samples is 244 houses, the minimum sample taken in the case area as many as 20 houses consisting of houses affected by dengue cases and houses around 19 houses with a radius of 50 meters.. The results of overlaying the density of Aedes spp. larvae in the area of RW 10, RW 16, RW 23, RW 25 and RW 28, Sendangmulyo Village is at a high risk of transmission with HI>10%. Whereas in RW 28 and RW 30 which have HI values of 9%, indicating that the two locations are sensitive or vulnerable to DHF (HI> 5%).